2021
DOI: 10.1111/ijcp.14945
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive mechanistic and therapeutic insight into the effect of chicory ( Cichorium intybus ) supplementation in diabetes mellitus: A systematic review of literature

Abstract: Background Cichorium intybus is a rich source of terpenoids and phenolic compounds, one of the effective methods in managing and reducing the complications of chronic diseases such as diabetes mellitus. The purpose of this systematic review was to evaluate the evidence obtained from animal and human studies on the effects of chicory on metabolic indicators (such as inflammation, oxidative stress, blood sugar and dyslipidaemia) of diabetes mellitus. Materials and methods This systematic search was performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…In contrast, administering PEE and CWE ameliorates male infertility by improving glycemic markers. Our results provide strong support for previous studies suggesting the antidiabetic actions of Purslane [ 124 , 133 ] and Chicory extracts [ 134 , 135 ]. Interestingly, Chicory root is the most abundant source of dietary fiber inulin, representing about 68% of the total compounds in fresh Chicory roots.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, administering PEE and CWE ameliorates male infertility by improving glycemic markers. Our results provide strong support for previous studies suggesting the antidiabetic actions of Purslane [ 124 , 133 ] and Chicory extracts [ 134 , 135 ]. Interestingly, Chicory root is the most abundant source of dietary fiber inulin, representing about 68% of the total compounds in fresh Chicory roots.…”
Section: Discussionsupporting
confidence: 91%
“…Although some investigations have been carried out to evaluate the anti-diabetic properties of the leaf extracts of the studied plants [18,19,20], only a few research papers used purslane and chicory leaf powders. Still, they did so at high levels (5-20%).…”
Section: Introductionmentioning
confidence: 99%
“…However, this strategy alone cannot reduce the growing prevalence of the disease [13]. Many studies have shown that natural and herbal compounds effectively reduce the symptoms of diseases, such as neurodegenerative disease, diabetes, neurological diseases, and fatty liver [14][15][16][17][18][19][20][21]. Plant-derived natural substances such as phenolic compounds, anthocyanin, wogonin, glycyrrhizin, green tea, coffee, garlic, soybean, and fenugreek might improve NAFLD [22][23][24].…”
Section: Introductionmentioning
confidence: 99%